Carbon monoxide packaging shows the same color improvement for dark cutting beef as high oxygen packaging. (March 2018) - Zhang, Yimin; Qin, Libo; Mao, Yanwei; Hopkins, David L.; Han, Guangxing; Zhu, Lixian; Luo, Xin
Abstract: In this study, carbon monoxide (CO) modified atmosphere packaging (MAP) was used to increase redness ( a *) and lightness ( L *) values of dark cutting beef (ultimate pH (pHu) ≥ 6.10), compared to normal pHu beef and intermediate pHu beef (pH: 5.40–5.79; pH: 5.80–6.09, respectively) during 20 d chilled storage. Compared with HiOx-MAP, CO-MAP exhibited similar color improvement effects (increased L *, a *, b * values) for all pHu beef groupings. The metmyoglobin (MetMb) content was lower under CO-MAP than that of HiOx-MAP in normal pHu beef, but opposite effects were observed in dark, high pH beef. This result could not be explained by MetMb reducing ability (MRA) and lipid oxidation, as both parameters were higher in CO-MAP beef than either normal or high pHu beef, compared with HiOx-MAP. In conclusion, CO-MAP was effective to maintain the cherry red color for dark cutting beef, but the color improvement mechanisms might be different with HiOx packaging methods.